How effective are Suspicious Transaction Reporting System in Iraq? - Dahash, Qaid (Journal of Legal Sciences, 2025)
Purpose - A cornerstone of the global anti-money laundering framework is the requirement that financial institutions are obligated to file suspicious transactions reports (STRs) to financial intelligence units. This obligation has been established by the Financial Action Task Force (FATF) Recommendations, the European Community Directive, and also the Iraqi Anti-Money Laundering and Counter-Terrorism Financing (AML/CTF) Act No.39 of 2015. The objective of this Article is to evaluate the effectiveness of the anti-money laundering reporting regime in Iraq in respect of suspicious transaction reports.Design/methodology/approach - A descriptive approach is used to explore the result of the anti-money laundering (AML) process in Iraq. The research is based on the secondary data published in the Annual Reports of the Anti-Money Laundering and Combating the Financing of Terrorism Office in Iraq from 2016-2024 and Middle East and North Africa Financial Action Task Force (MENAFATF), Mutual Evaluation Report of Iraq in May 2024, which covers the period 2018-2022.Findings - It is evident that the effectiveness of the Iraqi reporting suspicious transactions regime is questionable, given the relatively low number of STRs reported in light of the country's large exposure to high level of corruption, drug trafficking, fraud, human trafficking and other unlawful activities.Research limitations/implications - The assessment of Iraqi STR regime is limited due to the lack of reliable statistics regarding the scope of money laundering (ML) activities.Originality/value - There exists a considerable scarcity of scholarly research evaluating the reporting suspicious transaction regime under the Iraqi AML/CTF Act. Therefore, this Article seeks to provide an examination of the effectiveness of the Iraqi STRs regime. It is hoped that the study offers insights for researchers, banks, practitioners, and policymakers in Iraq.